Analysis of induced sputum in adults with asthma: identification of subgroup with isolated sputum neutrophilia and poor response to inhaled corticosteroids. Issue 10 (1st October 2002) - Green, R H; Brightling, C E; Woltmann, G; Parker, D; Wardlaw, A J; Pavord, I D
Abstract : Background: The debate as to whether asthma is a single or heterogeneous disease remains unresolved although pathological studies, mostly using fibreoptic bronchoscopy on small numbers of subjects, have emphasised the similarities between different clinical phenotypes. Methods: Lower airway inflammation was assessed non-invasively using induced sputum in 34 normal controls and 259 adults with symptomatic asthma receiving treatment at steps 1–3 of the British Thoracic Society (BTS) guidelines. A subgroup of 49 patients treated with as required β2 agonists only who met BTS criteria for a step up in treatment were studied before and 2 months after treatment with inhaled budesonide 400 μg twice daily. Results: There was considerable heterogeneity in induced sputum cell counts, particularly in non-atopic patients. A subgroup of 60 patients had a distinctive sputum cell profile with a neutrophil count higher than our normal range (>65.3%) and a normal sputum eosinophil count (<1.9%). These patients were older, predominantly female, and were more likely to be non-atopic but otherwise had similar clinical and physiological features to the group as a whole. Among the 49 subjects studied before and after inhaled budesonide, 11 patients had an isolated sputum neutrophilia. Following treatment, these patients showed significantly less improvement in visual analogue symptom scores (–5.5 v –19.4 mm; mean difference 13.9; 95% CI 0.7 to 27.0), forced expiratory volume in 1 second (FEV1 ) (–0.08 v 0.13 l; mean difference 0.21; 95% CI 0.03 to 0.39), and concentration of methacholine provoking a fall in FEV1 of 20% or more (PC20 ) (0.15 v 1.29 doubling doses; mean difference 1.11; 95% CI 0.13 to 2.15) than the remaining 38 patients. Conclusions: These results suggest the presence of a distinct subgroup of patients with mild to moderate asthma who have predominantly neutrophilic airway inflammation and who respond less well to treatment with inhaled corticosteroids.